ATTITUDES AND PRACTICES OF NURSING STUDENTS CONFRONTED WITH BLOOD EXPOSURE ACCIDENTS IN ABIDJAN - Kra, O.; Kadiané, N J; Aba, Y T; Koné, D.; Ouattara, B.; Bissagnéné, E. (African Journal of Infectious Diseases (AJID), 2015)
Background: Blood Exposure Accidents (BEAs) are frequent in healthcare settings and may cause such severe consequences as HIV andHepatitis B and C infections.Objective: to determine the attitudes and practices of nursing students facing BEAs.Materials and Methods: this was a cross-sectional prospective study conducted from August 16 to 23, 2011 at the “Institut National deFormation des Agents de la Santé d’Abidjan” (the National Institute in charge of training Health Workers). Data were collected by means ofself-administered questionnaires.Results: out of 266 student nurses included in the study, 73.3% were females while 26.7% were males. Their mean age was 29 years [20 years -37 years]. A previous training was conducted on BEAs for 67.3% of nursing students. Those students who were immunized against hepatitis Bwere 75.2%. Needle recapping was practiced by 43.6% of nursing students. Unclean needles were eliminated in containers by 96.2% of thestudents and waste containers were within close reach of only 65.4%. Glove wearing was systematic in 77.1% of the students. Before the survey38% of nursing students had been victim of BEAs at least once. Those BEAs were not reported in 68.3% of the victims.Conclusion: the attitudes and practices of nursing students are inadequate with regards to BEAs. A module on Hospital Hygiene is necessary inview of improving the training of nursing students.